2003
DOI: 10.1073/pnas.1331358100
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neuropathic pain responses in mice lacking the chemokine receptor CCR2

Abstract: Mice lacking the chemokine receptor chemotactic cytokine receptor 2 (CCR2) have a marked attenuation of monocyte recruitment in response to various inflammatory stimuli and a reduction of inflammatory lesions in models of demyelinating disease. In the present study, we compared nociceptive responses in inflammatory and neuropathic models of pain in CCR2 knockout and wildtype mice. In acute pain tests, responses were equivalent in CCR2 knockout and wild-type mice. In models of inflammatory pain, CCR2 knockout m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
532
4
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(570 citation statements)
references
References 33 publications
23
532
4
4
Order By: Relevance
“…Previous studies following axotomy of primary afferent sensory nerves has been shown to promote the activation and migration of macrophages within the peripheral nerve (Myers et al, 1996;Tofaris et al, 2002;Abbadie et al, 2003) and associated DRG (Hu & McLachlan, 2002). The increased number of macrophages observed may be due to proliferation of resident macrophages or due to infiltration of hematogeneous macrophages into the DRG (Mueller et al, 2003).…”
Section: Cellular Alterations In Satellite Cells Macrophages and Schmentioning
confidence: 77%
“…Previous studies following axotomy of primary afferent sensory nerves has been shown to promote the activation and migration of macrophages within the peripheral nerve (Myers et al, 1996;Tofaris et al, 2002;Abbadie et al, 2003) and associated DRG (Hu & McLachlan, 2002). The increased number of macrophages observed may be due to proliferation of resident macrophages or due to infiltration of hematogeneous macrophages into the DRG (Mueller et al, 2003).…”
Section: Cellular Alterations In Satellite Cells Macrophages and Schmentioning
confidence: 77%
“…Animal models of neuropathic pain have shown that nerve injury induces a host of pronociceptive, neuroplastic changes, including an upregulation of dynorphin in the spinal cord, enhanced levels of cholecystokinin, increased activation of phosphorylated p38 MAP kinase, and increased content and evoked release of substance P and CGRP. [1][2][3][4]10,34,52,66,80 Upregulation of cytokine receptor mRNA in the sciatic nerve and dorsal root ganglion after partial spinal nerve ligation has been noted, and SNL has also been reported to decrease MOR density in injured peripheral axons in the ipsilateral Lamina I of dorsal horn, leading to changes in presynaptic-and postsynapticevoked responses of MOR-containing fiber. 2,46,59 These synaptic changes include a decrease in presynaptic MOR-mediated inhibition, reduced inhibition of the miniature EPSP in substantia gelatinosa neurons, a shortened afterhy-perpolarization duration in C-fibers in the L 5 dorsal root ganglion, and increased repetitive firing of Aδ-fibers during sustained depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve injury increases MCP-1 expression in the DRG (Tanaka et al, 2004;White et al, 2005;Zhang & De Koninck, 2006). Mice lacking CCR2 show an impaired neuropathic pain (Abbadie et al, 2003). Intrathecal injection of MCP-1 activates microglia in wild-type but not in CCR2-deficient mice .…”
Section: The Role Of Microglia In Pain Controlmentioning
confidence: 98%
“…Fortunately, in last several years, we have seen several potential markers, such as the ATP receptor P2X4 (Tsuda et al, 2003), the chemokine receptors CCR2 (Abbadie et al, 2003) and CX3CR1 Zhuang et al, 2007), as well as Toll-like recepotor-4 (TLR4) (Tanga et al, 2005).…”
Section: Microglia Activation and Proliferation In The Spinal Cord Inmentioning
confidence: 99%